Analisis Desain Pesan Pembelajaran Pada Video Pembelajaran di Channel Youtube SDIT Cendekia Klaten - Wahyudi, Nanang Gesang Wahyudi (Madaniyah, 2023)
This research aims to determine the application of learning message design to learning videos that are available on the SDIT Cendekia Klaten YouTube channel. This type of research is content analysis research with descriptive method. The results of the study show that the implementation of the five principles of message design in learning videos on the YouTube channel at SDIT Cendekia Klaten has not been optimally implemented. It is proven that there are still several principles that have not been implemented, namely the principle of active student participation and feedback. In addition, the learning videos displayed are still not varied. Namely, learning simulation videos are still dominant. It is advisable to develop learning videos in the form of plays, tutorials or short films. In addition, in video media, it is necessary to consider the attitude of the audience, cultural background, age, gender and their expectations.